Exploring an illustrative national pathway for Guatemala to achieve food and climate targets in the framework of the FAO Global Roadmap - Ximena, Villagrán de León; Lilia Elena, García; Chemarin, Charlotte; Jones, Sarah K (2025)
The Sustainable Economic Observatory at Universidad Del Valle de Guatemala (UVG), and the Alliance of Bioversity International and CIAT as part of the FABLE Secretariat, collaboratively developed an illustrative national food and land use pathway for Guatemala incorporating actions that were prioritized with agriculture, health, environment and development ministries, NGOs, and farmer associations.